KIF2C Deletion Causes Meiotic Abnormalities and Nonobstructive Azoospermia in Mice - Hiroaki Kitakaze; Haruhiko Miyata; Yuki Oyama; Chen Pan; Yuma Kujime; Go Tsujimura; Takahiro Imanaka; Sohei Kuribayashi; Norichika Ueda; Kentaro Takezawa; Shinichiro Fukuhara; Norio Nonomura; et al. (Reproductive Medicine and Biology)
ABSTRACT Purpose Kinesin Family Member 2C (KIF2C) is a key regulator of microtubule dynamics and chromosome segregation in mitosis. However, its role in spermatogenesis remains unclear. Recent transcriptomic analyses suggest a potential link between KIF2C and male infertility. This study aimed to clarify KIF2C's roles in spermatogenesis using Kif2c knockout (KO) mice. Methods To overcome the preweaning lethality associated with Kif2c deletion, we generated Kif2c KO mice with a mixed genetic background of 129X1/SvJ and B6D2. We assessed male fertility, epididymal sperm counts, and testicular sections of Kif2c KO mice. Results Global Kif2c KO mice were obtained and showed male infertility. Histological analyses and epididymal sperm count revealed that Kif2c KO mice exhibited severely impaired spermatogenesis and absence of mature spermatozoa. These findings are consistent with those observed in patients with nonobstructive azoospermia (NOA). Our classification of Kif2c KO seminiferous tubules indicated that most spermatogenic cells were arrested at the early stages, particularly during meiosis. Conclusions This study provides in vivo evidence that KIF2C is essential for spermatogenesis and male fertility in mice. The successful generation of global Kif2c KO mice establishes an animal model for NOA, supporting research on germ cell development and reproductive health.